PERBANDINGAN PENGARUH MANAJEMEN HIGIENIS TERHADAP PRESTASI KERJA GURU SMK NEGERI 1 MEDAN DENGAN SMK NEGERI 5 MEDAN - Muhammad Rahmat Hidayat; Cut Devi Maulidasari (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2019)
This research is a study about hygienic management towards teachers’ work result in SMK Negeri 1 Medan against SMK Negeri 5 Medan. This research made by the deductive thought with the model of Comparative Corelational analysis. The samples between research location are 70 samples of respondent in SMK Negeri 1 Medan and 66 samples of respondent in SMK Negeri 5 Medan.Data collected between locations effort the result hypothetically using t-test method. The research comparing the R square, t-test value, and Sig. between research locations and got the answer of hypothesis. Results of the analysis showed that there is a relation between hygienic management to teachers’ work result in SMK Negeri 1 Medan with t-test result (13.020) > t-table (2,080) and Sig. 0,000 < 0,05. In another location as in SMK Negeri 5 Medan t-test result (9.000) > t-table (2,080) and Sig. 0,000 < 0,05. The comparing result based on t-test result, Sig. and coefficient determination shown the different result between locations.